Experimental Parametrization of Magma Mixing: Application to the ad 1530 Eruption of La Soufrière, Guadeloupe (Lesser Antilles). (15th March 2018) - Pichavant, M; Poussineau, S; Lesne, P; Solaro, C; Bourdier, J -L
ABSTRACT: New petrological data on eruption products and experimental results are integrated and a model for the evolution of the La Soufrière (Guadeloupe, Lesser Antilles arc) magma reservoir prior to the ad 1530 eruption is presented. In comparison with recent volcanic crises in the Antilles, the ad 1530 eruption is distinctive. The eruptive pyroclastic sequence shows a continuous zonation in whole-rock composition from silicic (∼62 wt % SiO2 ) to mafic andesite (∼55 wt % SiO2 ). Mafic products are estimated to be 80% of the total eruption volume. All juvenile clasts are crystal-rich (46–60 vol. % phenocrysts), the crystallinity being inversely correlated with the bulk-rock SiO2 content. The phenocryst assemblage (plagioclase, orthopyroxene, clinopyroxene, magnetite) is constant throughout the sequence. Complexly zoned crystals are encountered, but An60–65, En56–59 and Mt66–68 compositions occur in all samples. Glass inclusions are rhyolitic with up to 5–5·5 wt % H2 O. Matrix glasses are strongly heterogeneous, from ∼64 to >76 wt % SiO2 . The pre-eruptive evolution of the reservoir is dominated by the remobilization of a resident andesitic body following the arrival of a basaltic magma batch. Conditions of early remobilization are constrained from experiments on a basalt from the L'Echelle scoria cone. The arrival magma is a crystal-poor, moderately hot (975–1025°C), wet (>5 wt % H2 O) and oxidized (NNO + 1, where NNO is nickel–nickel oxide buffer) low-MgO high-alumina basalt similar to those involved in other Antilles volcanic centers. Geothermometry and experiments on a silicic andesite product of the eruption show that, for melt H2 O contents between 5 and 5·5 wt %, phenocrysts and interstitial melt in the resident magma were in mutual equilibrium at ∼875°C and NNO + 0·8. However, matrix glass and glass inclusion compositions show that, locally, the andesite body was as cold as 825°C. Melt volatile concentrations imply a minimum depth for the magma reservoir between 5·6 and 7·1 km, and the absence of amphibole phenocrysts indicates a maximum depth at 8·5 km. The ad 1530 eruption tapped a hybrid magma assembled by mixing approximately equal proportions of resident andesite and arrival basalt. Mineralogical indicators of the mixing event include An-rich layers in plagioclase, En-rich rims on orthopyroxene and core–rim zonation in magnetite, but overall phenocrysts were little modified during assembly of the hybrid magma. In comparison, matrix glasses were more severely affected. Mixing proceeded essentially by the addition of a mafic melt to the andesite body. The continuous chemical zonation observed in ad 1530 eruption products reflects mixing between three components (mafic melt, silicic melt, phenocryst assemblage). Timescales measured on different eruptive products range from several thousand years (U–Th–Ra disequilibria) to tens of days (diffusion modelling in orthopyroxenes) and to tens of hours (heterogeneous matrix glasses). Short timescales since mafic recharge, lack of extensive transformations of phenocrysts, continuous whole-rock chemical zonation and predominance of mafic products are all consistent with triggering of the ad 1530 eruption by a major mafic recharge event that originated in the middle to lower Lesser Antilles arc crust.